Pengembangan Model Pembelajaran Daring Berbasis Collaborative Skills - Tejo Nurseto; Ahmad Chafid Alwi; Sulasmi Sulasmi (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
This study aims to develop an online learning model based on Collaborative skills which is expected to provide solutions in preparing graduates who have 21st century skills in collaboration skills. This model was developed using the ADDIE method. At the analysis stage before developing the model, exploratory factor analysis was conducted and it was found that overall the four domains/factors had a cumulative percentage of 62.25%. Four factors are able to measure the variable by 62.25%, the rest is measured by other factors. The collaborative skill profile has the lowest score in the formulating domain with indicators of implementation of elaboration in discussion with a score of 69.71 and the highest score in the forming domain, which encourages all members to actively participate with a score of 89.92. At the design stage, this learning is designed in synchronous online learning. The developed model is a jigsaw type collaborative learning model which is carried out online based on collaborative skills. Skills which include forming, functioning, formulating and fermenting are explicitly included in the Jigsaw process that is run online. Based on the results, an effectiveness test was carried out in the experimental class compared to the control class using an independent sample T-Test, N-Gain Score and audience validity test, a significance score of 0.022 was obtained, which means that there is a difference between the experimental and control classes, N-Gain score of 0.056 which means the effectiveness is moderate, and based on the audience's assessment of 88% (very effective).DOI: https://dx.doi.org/10.17977/UM014v15i12022p001